2023
DOI: 10.4236/ojmp.2023.123007
|View full text |Cite
|
Sign up to set email alerts
|

Association between Support and Satisfaction with Life among Older Adults in Ekiti, Nigeria: Findings and Implications

Abstract: Many developing countries like Nigeria lack policy for the care of the older adults and this creates major challenges for the elderly population. The traditional family institution and community support that used to be safety nest are being adversely affected by westernization. This development might have adverse effect on life satisfaction among the older adults. This hospital based cross-sectional study was designed to determine the association between support and life satisfaction among older adults. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Our study’s findings indicate that life satisfaction decreases with age (65-74, 75-84, 85+), with the oldest-old (85+) being the least satisfied. These findings resonate with previous studies in Ekiti State (Adebayo & Arogundarde, 2011; Aina et al, 2023), affirming the consistency of our results with those of the southwestern State of Nigeria. This observation accentuates the challenges posed by resource constraints among these golden-agers.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study’s findings indicate that life satisfaction decreases with age (65-74, 75-84, 85+), with the oldest-old (85+) being the least satisfied. These findings resonate with previous studies in Ekiti State (Adebayo & Arogundarde, 2011; Aina et al, 2023), affirming the consistency of our results with those of the southwestern State of Nigeria. This observation accentuates the challenges posed by resource constraints among these golden-agers.…”
Section: Discussionsupporting
confidence: 93%
“…Such findings accentuate the importance of policy initiatives and interventions to enhance the mental well-being of older individuals in resource-constrained settings such as the Ekiti State. The consistency of these findings with those of prior studies in Ekiti State and southwestern Nigeria (Adebayo & Arogundarde, 2011; Aina et al, 2023) strengthens the robustness and validity of the results. This finding suggested that the observed age-related decrease in life satisfaction is not an isolated phenomenon but aligns with broader regional studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations